Information Support of State Policy as the Most Important Factor of State Security - Torichniy , Vadym (Pressing Problems of Public Administration, 2019)
Information support is a special kind of provision, due to the speci city of the provisioning product itself - information. Information resources in recent decades have become increasingly important in the functioning of modern states. It is not by chance that at the dawn of human civilization, two areas of activity were distinguished in its development: material production and the intensi cation of information processes. The purpose of the article is to study information support as a special type of management, which is based on the role of information in the activities of public authorities and its impact on the security problems of the state. Ensuring national security involves the implementation of a complex set of various activities: political and diplomatic, government and management, economic, legal, military and informational, aimed at achieving and maintaining its necessary state. The effectiveness of such activities is largely determined by the presence of stable information links, the number of information  ows, their nature, content and quality, that is, information support for national security. The speci city and distinctive feature of information support from other types of national security is in the product itself - information, since the latter is the basis of any human activity and therefore is a necessary condition for its rational life support. Thus, national security is a complex, dynamic, integral social system, the components of which are the security subsystems: the state, the individual, and the society. Thus, it should be emphasized that the formation of a security policy, the development and implementation of its conceptual and doctrinal foundations is a complex and complex process that is carried out in a law-based state on a democratic basis. It means that the information security of national security in this sense is called upon to equally provide access to information for various political parties and their equilibrium information impact on government bodies and government.